2015
DOI: 10.1124/mol.114.096701
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Throughput Analysis Demonstrates that Chemicals with Distinct Seizurogenic Mechanisms Differentially Alter Ca2+ Dynamics in Networks Formed by Hippocampal Neurons in Culture

Abstract: Primary cultured hippocampal neurons (HN) form functional networks displaying synchronous Ca 21 oscillations (SCOs) whose patterns influence plasticity. Whether chemicals with distinct seizurogenic mechanisms differentially alter SCO patterns was investigated using mouse HN loaded with the Ca 21 indicator fluo-4-AM. Intracellular Ca 21 dynamics were recorded from 96 wells simultaneously in real-time using fluorescent imaging plate reader.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Consistent with our previous report (Cao et al, 2015), we found that HN neurons produced characteristic patterns of spontaneous synchronous Ca 2+ oscillations (SCOs) as they developed network complexity (Fig. 2A&C).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our previous report (Cao et al, 2015), we found that HN neurons produced characteristic patterns of spontaneous synchronous Ca 2+ oscillations (SCOs) as they developed network complexity (Fig. 2A&C).…”
Section: Resultssupporting
confidence: 92%
“…This method permitted a high temporal resolution (every half second) recording of internal Ca 2+ concentration to reveal SCO dynamics in parallel across 96 wells before and after exposure to TETS (Cao et al, 2015). After aspirating the medium, a volume of 100 μl of Locke’s buffer (in mM: 8.6 HEPES, 5.6 KCl, 154 NaCl, 5.6 glucose, 1.0 MgCl 2 , 2.3 CaCl 2 , and 0.1 glycine, pH 7.4) containing Fluo-4 (4 μM) and BSA (1 mg/ml) was added to each well immediately and incubated in a 37 °C CO 2 incubator for 1h.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cultures offer significant advantages and flexibility for not only defining temporal patterns of network excitation and neuropathology but also enabling systematic analysis of the inherent physiological responses of neurons and astrocytes in isolation or in coculture that protect against or promote toxicity of threat agents (Fig. ) . Such cultures develop elaborate neuronal networks with functional synapses whose activity can be quantitatively monitored in real time using three complementary approaches: two that use fluorescent indicators to monitor intracellular Ca 2+ or membrane potential using the 96‐well FLIPR® Tetra imager and a third that measures electrical spike activity in cultures plated on MEA.…”
Section: Rapid‐throughput In Vitro Models Of Neural Network Hyperexcimentioning
confidence: 99%
“…Microscopic imaging techniques are used to test how threat agents and interventions directly influence asynchronous Ca 2+ events from pure astrocytic cultures . We discovered that acute challenge of mouse hippocampal cultures enriched in neurons with TETS, a GABA A R blocker; kainate, an AMPA/kainate receptor agonist; 4‐aminopyridine (4‐AP), a K + channel blocker; or pilocarpine, a muscarinic acetylcholine receptor agonist, caused distinct changes in SCO dynamics . Importantly, TETS‐triggered changes in SCO patterns have provided a basis for screening compounds, including benzodiazepines and neurosteroids, as novel therapeutic interventions that may be more efficacious than the current standard of care for TETS intoxication …”
Section: Rapid‐throughput In Vitro Models Of Neural Network Hyperexcimentioning
confidence: 99%